High field side lower hybrid wave launch for steady state plasma sustainment. (2nd November 2018) - Bonoli, P.T.; Wallace, G.M.; Shiraiwa, S.; Baek, S.G.; Doody, J.; Greenwald, M.; LaBombard, B.; Leccacorvi, R.; Filar, K.; Lin, Y.; Marmar, E.; Meneghini, O.; et al.
Abstract: This paper explores how the use of waves in the lower hybrid range of frequencies (LHRF) alleviates many unresolved current drive issues when launched from the high field side (HFS) of a tokamak. Efficient, robust, reliable, steady-state current drive is a requirement for a viable tokamak fusion reactor. Launching LHRF waves from the HFS opens the 'accessibility window', allowing for use of a lower parallel refractive index, , for a given plasma density and on-axis magnetic field. The lower waves damp in a region of higher temperature, resulting in increased current drive efficiency and a damping profile shifted closer to the mid-radius as compared to low field side launch. Moving the LHRF antenna to the quiescent scrape off layer on the HFS reduces the likelihood of detrimental wave scattering from density fluctuations, as well as ameliorating the plasma-material-interaction and wave coupling challenges. Additional benefits with respect to fast particle and neutron fluxes can be realized by moving to the HFS. An engineering assessment of HFS launch shows that it is feasible to implement an HFS LHRF system on existing tokamaks, with fewer hurdles anticipated for future tokamaks built with HFS antenna systems integrated in the design from the start.